Effect of eight weeks aerobic endurance training (swimming) on long-distance freestyle performance among intermediate male swimmers - Balasooriya, B.K.H.S.; Nawodya, K.W.D.; De Silva, R.P.D.K. (University of Jaffna, 2024)
Swimming strokes are the different techniques used by swimmers to move throughthe water efficiently. In the last 2023 inter-university games, it was observed that the intermediate male team at Sabaragamuwa University had a problem with their performance in events of 200 meters and other long-distance events in freestyle. The problem was that they had considered the timing gap, lap by lap compared to othertop players. Therefore the objective of the study was to find out the effect of eight weeks of aerobic endurance training (swimming) on long distance freestyle performance among intermediate male swimmers in Sri Lanka. Two male intermediate long-distance swimmers from Sabaragmuwa University were selected using the purposive sampling technique to take part in the research. The training program was conducted over an eight-week period involving two intermediate male swimmers. Both samples completed training three days per week and two hours per day. The level of tested swimmers was assessed using the swimming beep test beginning and the end of the periodization as pre test and post-test. For descriptive analysis, only data obtained at maximum loads in both pre and post-tests were accepted. As expected study results showed that there was significant improvement evidenced in the post-test more than the pre-test. According to the norms table of the swimming beep test, both samples' performance was poor in the pre-test. However, in the post-test, both samples showed average performance. The above study concludes that the enhancement of the aerobic endurance of freestyle long-distance intermediate male swimmers at Sabaragamuwa University of Sri Lanka indicates the necessity to improve the performance of swimmers with proper training.
Keywords: Aerobic Endurance; Freestyle; Long Distance; Swimming Beep Test